Paternal Expressed Gene 10 (PEG10) is decreased in early-onset preeclampsia - Lydia Baird; Ping Cannon; Manju Kandel; Tuong-Vi Nguyen; Anna Nguyen; Georgia Wong; Cíara Murphy; Fiona C. Brownfoot; Elif Kadife; Natalie J. Hannan; Stephen Tong; Lucy A. Bartho; et al. (BMC, 2023)
Abstract Background Preeclampsia is a severe complication of pregnancy which is attributed to placental dysfunction. The retrotransposon, Paternal Expressed Gene 10 (PEG10) harbours critical placental functions pertaining to placental trophoblast cells. Limited evidence exists on whether PEG10 is involved in preeclampsia pathogenesis. This study characterised the expression and regulation of PEG10 in placentas from patients with early-onset preeclampsia compared to gestation-matched controls. Methods PEG10 expression was measured in plasma and placentas collected from patients with early-onset preeclampsia (< 34 weeks') and gestation-matched controls using ELISA (protein) and RT-qPCR (mRNA). First-trimester human trophoblast stem cells (hTSCs) were used for in vitro studies. PEG10 expression was measured during hTSC differentiation and hTSC exposure to hypoxia (1% O2) and inflammatory cytokines (IL-6 and TNFα) using RT-qPCR. Functional studies used PEG10 siRNA to measure the effect of reduced PEG10 on canonical TGF- $$β$$ β signalling and proliferation using luciferase and xCELLigence assays, respectively. Results PEG10 mRNA expression was significantly reduced in placentas from patients with early-onset preeclampsia (< 34 weeks' gestation) relative to controls (p = 0.04, n = 78 vs n = 18 controls). PEG10 protein expression was also reduced in preeclamptic placentas (p = 0.03, n = 5 vs n = 5 controls, blinded assessment of immunohistochemical staining), but neither PEG10 mRNA nor protein could be detected in maternal circulation. PEG10 was most highly expressed in hTSCs, and its expression was reduced as hTSCs differentiated into syncytiotrophoblasts (p < 0.0001) and extravillous trophoblasts (p < 0.001). Trophoblast differentiation was not altered when hTSCs were treated with PEG10 siRNA (n = 5 vs n = 5 controls). PEG10 was significantly reduced in hTSCs exposed to hypoxia (p < 0.01). PEG10 was also reduced in hTSCs treated with the inflammatory cytokine TNF $$α$$ α (p < 0.01), but not IL-6. PEG10 knocked down (siRNA) in hTSCs showed reduced activation of the canonical TGF-β signalling effector, the SMAD binding element (p < 0.05) relative to controls. PEG10 knockdown in hTSCs however was not associated with any significant alterations in proliferation. Conclusions Placental PEG10 is reduced in patients with early-onset preeclampsia. In vitro studies suggest that hypoxia and inflammation may contribute to PEG10 downregulation. Reduced PEG10 alters canonical TGF- $$β$$ β signalling, and thus may be involved in trophoblast dysfunction associated with this pathway.